(untitled) (Indonesian Journal of Science and Technology, 2025)
Empty fruit bunches (EFBs) discarded from the palm oil industry were converted into hydrochars with a high surface area via hydrolytic agent-assisted hydrothermal carbonization (HTC). The reaction temperature was varied (160, 200, 240, and 280 °C) for a constant reaction time of 2 h. The effects of the type of hydrolytic agent (H2O2 and H2SO4) on the hydrochar properties were investigated. The physical and chemical properties of the as-obtained hydrochars, such as surface area, porosity, morphology, functional groups, and elemental composition, were characterized. The results showed that the fixed carbon and carbon contents increased with increasing temperature. At 280 °C, the hydrochar produced via the H2SO4-assisted HTC process had the highest fixed carbon (38.35 wt.%) and carbon (72.65 wt.%) contents. In comparison, the hydrochar (O-EFB280h2) produced via the H2O2-assisted HTC process at 280 °C exhibited the highest surface area (479.19 m2/g) and pore volume (0.727 cm3/g), and it contained functional groups such as C-H, C=O, and C-O. The H2O2-assisted HTC process produced hydrochars with a high surface area that could be used in a variety of applications.